2019
DOI: 10.1530/jme-18-0104
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modulation of two melanocortin-5 receptors by MRAP2 proteins in zebrafish

Abstract: Melanocortin receptor accessory protein 2 (MRAP2) plays an important role in regulating melanocortin receptors. In zebrafish, MRAP2a and MRAP2b show distinct pharmacological effects on MC4R activity, but how MRAP2 protein regulates other zebrafish melanocortin receptors is barely studied. Zebrafish have two mc5r genes: mc5ra and mc5rb, it is still vague which one is the homologous isoform to the mammalian paralog. Here, we utilize synteny and phylogenetic analysis to demonstrate the evolutionary conservation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…MRAPs and MCRs have been reported to form homodimers in vitro (10, 27, 28, 29, 30). Our recent work demonstrated that zebrafish MC5Ra and MC5Rb could form homo- and heterodimers, which could be disrupted by MRAP2a or MRAP2b proteins (24). Therefore, we also conducted YFP luminescent assays and identified the formation of antiparallel homodimers of slMRAP2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRAPs and MCRs have been reported to form homodimers in vitro (10, 27, 28, 29, 30). Our recent work demonstrated that zebrafish MC5Ra and MC5Rb could form homo- and heterodimers, which could be disrupted by MRAP2a or MRAP2b proteins (24). Therefore, we also conducted YFP luminescent assays and identified the formation of antiparallel homodimers of slMRAP2.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then treated with a fixed concentration of α-MSH (2 nM) and different concentrations of AgRP in DMEM supplemented with 0.1% bovine serum albumin for 4 h at 37°C. The cAMP level was measured as described before (24) using the Dual-Glo Luciferase Assay System (Promega). Luminescence was measured with a Spectramax M5 plate reader.…”
Section: Methodsmentioning
confidence: 99%
“…In such cases, the respective contributions of monomers and dimers to the cellular signaling output are usually unclear, which hinders appropriate interpretation of, e.g., dose-response curves in terms of a dissection between monomer/oligomer mediated signaling. The potential functional relevance of oligomeric constellations is also confirmed for the zfMC5R, whereby receptor oligomerization is hindered by the protein interaction with zebrafish Mrap2 (114).…”
Section: Resultsmentioning
confidence: 80%
“…The MRAP family (MRAP1 and MRAP2) were originally identified to modulate the signaling and dimerization of the melanocortin receptor family in several species [ 29 , 30 , 31 , 32 , 33 , 34 ]. Recently, they were also found to regulate the trafficking and activity of several other non-melanocortin GPCRs (such as PKR1, OX1R and GHSR1a) [ 34 , 35 , 36 , 37 , 38 , 39 ]. Here, we transfected HEK293T cells with 3HA-SRIF1s and 2Flag-MRAP1/2 to determine whether MRAP1/MRAP2 could interact with SSTRs.…”
Section: Resultsmentioning
confidence: 99%